Valorisation of Shrimp Waste into Chitosan/Montmorillonite-Sulfosuccinic Acid Composite Membrane for DMFC Application - Shalahudin Nur Ayyubi; Lukman Atmaja; Aprilina Purbasari (Reaktor, 2021)
Composite membranes have been synthesized from biopolymer chitosan (CS) and nanosized montmorillonite (MMT) filler crosslinked with sulfosuccinic acid (SSA) as an alternative membrane electrolyte for direct methanol fuel cell (DMFC) application. All prepared membranes were obtained by solution casting technique. Prepared membranes were systematically characterized in terms of water uptake, methanol uptake, and methanol permeability as membrane performance parameter for DMFC applications. Fourier transform infrared spectroscopy was used to confirm the structures of the CS/MMT-SSA composite electrolyte membranes. The addition of sulfosuccinic acid evidently decreased the value of methanol permeability with the lowest value of 2.9973 × 10-7 cm2/s was obtained from CS/MMT-SSA 16% membrane. The addition of sulfosuccinic acid also decreased the absorption of methanol with the lowest value of 45.9459% while the water absorption of 53.6424% occurred in the membrane with the addition of 16% sulfosuccinic acid. As a result, the CS/MMT-SSA composite membrane appears to be a potential candidate for the DMFC applications.Keywords: direct methanol fuel cell; proton exchange membrane; methanol permeability; chitosan